2019
DOI: 10.5114/wiitm.2019.85360
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ureteroscopic lithotripsy: a case-control study and analysis of 385 cases of holmium laser ureterolithotripsy.

Abstract: Introduction: Ureteroscopic lithotripsy has become the first choice for the treatment of middle and lower ureteral stones, but it still has a certain rate of surgical failure. Here we aimed to determine the factors that may affect the success rate of holmium laser ureterolithotripsy (HLU) and provide the basis and guidance for its future use. Aim: To evaluate the risk factors for HLU failure. Material and methods: The clinical data of 385 patients undergoing holmium laser ureterolithotripsy from 2009 to 2012 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…3,9 There was no hydronephrosis in 19.5% cases and most of the patient with hydronephrosis had mild degree of hydronephrosis (54.3%). Similar to our study, a study done by Zheng et al 18 also showed that most of the patient had either no or mild hydronephrosis.…”
Section: Discussionsupporting
confidence: 92%
“…3,9 There was no hydronephrosis in 19.5% cases and most of the patient with hydronephrosis had mild degree of hydronephrosis (54.3%). Similar to our study, a study done by Zheng et al 18 also showed that most of the patient had either no or mild hydronephrosis.…”
Section: Discussionsupporting
confidence: 92%
“…In order to minimize surgical complications, certain studies have employed modi ed ureteroscopes equipped with suction sheaths. However, the distal end of these sheaths can only reach the pelviureteric junction and cannot extend into the renal pelvis or calyces, leading to low e ciency in stone retrieval [28].Moreover, the opening of the UAS is susceptible to obstruction, resulting in elevated pressure in the renal pelvis and re ux, thereby increasing the risk of bleeding and infection [31].Previous research has indicated that terminal bendable negative pressure suction sheaths, in comparison with conventional ureteroscopic sheaths, offer the advantage of exible entry into calyceal stones, allowing the front end of the sheath to be secured in the speci c calyx for accurate stone fragmentation and retrieval, with the aim of reducing residual stones and recurrence [28,32].The simultaneous suction feature not only aids in stone aspiration but, importantly, enables the prompt elimination of irrigation uids during surgery, maintaining a low-pressure environment in the renal pelvis to prevent severe intraoperative and postoperative infections [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ultrasound lithotripsy uses only rigid probes and rigid endoscopes, and its scope of application is mainly limited to kidney stones. Contact lithotripsy (pneumatic or electrokinetic lithotripters) is one of the most effective and safe methods of contact destruction of stones 11 , 12 . At the same time, the use of such lithotripters is also limited by rigid endoscopes, and retrograde stone propulsion in transurethral lithotripsy is a disadvantage of the method 11 – 13 .…”
Section: Introductionmentioning
confidence: 99%